2010
DOI: 10.1160/th10-01-0043
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of the prostaglandin E2 receptor subtype EP2 or EP4 leads to inhibition of platelet aggregation

Abstract: The effect of selective activation of platelet prostaglandin (PG) E2 receptor subtype EP2 or EP4 on platelet aggregation remains to be determined. In platelets prepared from wild-type mice (WT platelets), high concentrations of PGE2 inhibited platelet aggregation induced by U-46619, a thromboxane receptor agonist. However, there was no significant change in the inhibitory effect of PGE2 on platelets lacking EP2 (EP2-/- platelets) and EP4 (EP4-/- platelets) compared with the inhibitory effect on WT platelets. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Values are mean of duplicate determinations of one experiment influence platelet function in human blood [25]. Another difference of murine and human platelets has been observed recently by Kuriyama et al, who found a much higher inhibitory potency of a selective EP 4 -receptor-agonist in human platelets as compared to murine platelets [16]. Those disparities draw attention to the limits of comparison of mouse and human platelets.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Values are mean of duplicate determinations of one experiment influence platelet function in human blood [25]. Another difference of murine and human platelets has been observed recently by Kuriyama et al, who found a much higher inhibitory potency of a selective EP 4 -receptor-agonist in human platelets as compared to murine platelets [16]. Those disparities draw attention to the limits of comparison of mouse and human platelets.…”
Section: Discussionmentioning
confidence: 84%
“…It is often propagated that PGE 2 shows a biphasic effect on platelets: low PGE 2 concentrations potentiate platelet aggregation via EP 3 activation, whereas higher lM concentrations inhibit platelet aggregation via EP 2 /EP 4 activation [13,14,16,17,24,26,31,32]. The biphasic effect is apparently more pronounced in mice platelets [13,14,16,17], whereas studies with human platelets show less consistent results [26,29,32,33]. Our recent investigation of the effect of PGE 2 on platelets in human blood clearly showed no potentiation of platelet aggregation by low PGE 2 concentrations, and only a slight inhibition at high concentrations (5 lM) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iloprost is an EP1 agonist, but is poorly selective [57]. Newer synthetic EP receptor agonists include ONO-DI-004 (EP1) [58], ONO-AE1-259 (EP2) [58, 59], ONO-AE-248 (EP3) [60], and ONO-AE1-329 (EP4) [60]. Novel EP receptor antagonists include ONO-8713 (EP1) [58], ONO-AE3-240 (EP3) [61], DG-041 (EP3) [62], ONO-AE208 (EP4) [63], and MF-191 (EP4) [56].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EP2 stimulation leads to inhibition of platelet aggregation. The selective EP2 agonist ONO-AE1-259 inhibits platelet aggregation [58, 59]. This inhibitory effect is also seen with the EP2 agonist butaprost [56].…”
Section: Introductionmentioning
confidence: 99%